Symposium 2: Looking for black cats and lessons from Charlie: Exploring the potential of public click pedagogy - Bigum, Chris; Rowan, Leonie; Hamilton, Mary; Wright, Steve; Haxell, Ailsa (Proceedings of the International Conference on Networked Learning, 2014)
This paper is about a slow hunch. A hunch that a modest interference in networked learning, that we have called public click pedagogy (PCP), may, in some instances, usefully open up a side of networked learning that is often glossed. Learning new material, developing new skills, making new discoveries can be complicated, and messy. Few of us go from inexperienced to skilled or novice to master in anything like a simple, tidy or routine manner. We often learn more from our mistakes than our successes. We sometimes find ourselves in blind alleys or chasing down rabbit holes that appear to take us nowhere. What learners actually do when they try to come to terms with a new domain via formal or informal means, tends to be secret learner business. What is commonly made visible is how successful they are in coming to terms with the domain, something which is judged by people who have demonstrated knowledge and expertise in the domain. Our hunch is that a modest exploration of secret learner business by making public the fuzzy, pragmatic and messy business of learning may work as a useful complement to those elements of learning already made public. The label PCP draws attention to three characteristics of this work: that it is made public, that ‘aha’ or click moments which in a glossed account masquerade as the product of acute insight are traced carefully, and that accounts of these practices may operate pedagogically, for the learner, and perhaps, other learners. To explore the doing of networked learning we draw parallels with the doing of science as it has been studied by scholars in the field of science, technology, and society (STS). Looking at how scientists actually do science, STS scholars came to see that accounts of science as products of the scientific method glossed the messiness, noncoherence and fuzziness of what went on in the laboratory. To Bruno Latour, in the early days of STS, science was Janus-like, with two contradictory faces: science in the making and ready made science. More recently, John Law with others have extended this line of argument to examine the performativity of noncoherence. Drawing on this work, we examine three empirical cases, one of which is the preparation of this paper. We trace the negotiation of the ideas and arguments, our learning in the making, and the noncoherences which we partially domesticate through dialogue.